Sleep Matters: CD4+ T Cell Memory Formation and the Central Nervous System. Issue 8 (August 2019) - Lange, Tanja; Born, Jan; Westermann, Jürgen
Abstract : The mechanisms of CD4 + T-cell memory formation in the immune system are debated. With the well-established concept of memory formation in the central nervous system (CNS), we propose that formation of CD4 + T-cell memory depends on the interaction of two different cell systems handling two types of stored information. First, information about antigen (event) and challenge (context) is taken up by antigen-presenting cells, as initial storage. Second, event and context information is transferred to CD4 + T cells. During activation, two categories of CD4 + T cell develop: effector CD4 + T cells, carrying event and context information, enabling them to efficiently focus their response to tissues under attack; and persisting CD4 + T cells, providing context-independent antigen-specific memories and long-term storage. This novel hypothesis is supported by the observation that mammalian sleep can improve both CNS and CD4 + T-cell memory. Highlights: As in the CNS, in the immune system two principal types of information can be distinguished: context information concerning the milieu during activation and event information regarding the structure of the antigen. During CD4 + T cell memory formation, information is transferred from the initial store (i.e., APCs expressing peptide–MHC II complexes) to the long-term store (i.e., CD4 + T cells expressing cognate TCRs). In the course of information transfer, context information is lost and event information is stored in an abstracted form. Sleep supports both neurobehavioral and immunological memory formation. Modulation of T cell traffic is one likely mechanism by which sleep can affect memory formation.